a-reum: the Korean bojagi reimagined - Hur, So Hyun (Nanyang Technological University, 2024)
‘a-reum’ is a cultural design project inspired by traditional Korean art, symbols and motifs. a-reum explores a journey through Korean heritage and a contemporary fashion adaptation, by delving into the intricate world of bojagis (wrapping cloths). The designed bojagis act as a testament to the fusion of traditional motifs curated to encapsulate a distinct visual ‘Korean-ness’ while bridging past and present, tradition and modern style.